Nursing students' assessment of pain and decision of triage for different ethnic groups: An experimental study - Chan, J.; Hamamura, Takeshi (Churchill Livingstone, 2015)
Background: Pain management is a priority in nursing care but little is known about the factors that affect nursing students' assessment of pain expressed by patients of different ethnic backgrounds. Objectives: This study examined undergraduate nursing students' assessment of pain and decision of triage when pain was expressed in different languages and their relation to students' empathy and social identity. Comparison between students with and without clinical experience was also carried out. Design: This is a cross-sectional quantitative design. Setting: This study took place at a university in Hong Kong. Participants: 74 female undergraduate nursing students. Methods: Students listened to eight audio recordings in which an individual expressed pain in one of the two dialects of Chinese, either Cantonese or Putonghua. For each dialect, two recordings depicted mild pain and two depicted severe pain. After listening to each recording, students rated the pain level and indicated their decision of triage. Subsequently, students completed a questionnaire that measured their empathy and social identity and reported their demographics. The data were analyzed by descriptive statistics, correlational analyses, and t-tests.Results: Severe pain described in Putonghua was rated as more intense than that described in Cantonese but it was not classified as more urgent. Students with clinical experience tended to perceive mild pain as less painful and less urgent than those without clinical experience. For mild pain described in Cantonese, students with clinical experience evaluated it as more urgent than those without such experience. The empathy level of students with and without clinical experience was comparable. Students with more empathy, especially those without clinical experience, reported heightened perceived intensity of severe pain described in Putonghua. Conclusions: Nurse educators should note that empathy, social identity, and clinical experience may alter students' pain assessment of patients from different ethnicities. Pain education needs to be reinforced.